The Effect of Inflation and Firm Size on Profitability in Banking Companies Listed on The Stock Exchange - Nofitasari, Susi; Haruman Putri, Risa (Journal of Business Administration and Strategy, 2025)
This study analyzes the effect of Inflation and Firm Size on Profitability in Banking Companies listed on the Indonesia Stock Exchange. The research method used is multiple linear regression analysis, which is to determine the effect of two independent variables on one dependent variable which is then carried out t hypothesis test and F hypothesis test to determine the significance level of the effect. The population of this study is the financial statements of Banking Companies listed on the Indonesia Stock Exchange and samples taken using purposive sampling techniques so that the samples taken start from the 2019-2023 period. Based on the results of the study, it shows that simultaneously and partially Inflation and Firm Size have a positive and significant effect on Profitability. The coefficient of determination is 36.3% and the remaining 63.7% is another variable that also affects profitability but is not examined. As for partial Inflation has a greater influence than Firm Size.